Hepatoprotective effects of lychee (Litchi chinensis Sonn.): A combination of antioxidant and anti-apoptotic activities - Bhoopat L. (2014)
Aim of the study: Gimjeng and Chakapat lychee (Litchi chinensis Sonn.) were evaluated for hepatoprotective activity on CCl4-induced hepatotoxicity in rats. Materials and methods: Fruit pulp extracts of the lychees were examined for vitamin C, phenolic contents, anti-lipid peroxidation activity and hepatoprotective effect. Male Wistar albino rats were intraperitoneally injected (ip) with CCl4 (2 ml/kg), then were orally administered (po) with silymarin (100 mg/kg), and Gimjeng or Chakapat extracts (100 and 500 mg/kg). After ten days, the rats were sacrificed and their livers were examined histopathologically and immunohistochemically. Their serum glutamate-pyruvate transaminase, glutamate-oxalate transaminase, and alkaline phosphatase activities were analyzed. Apoptotic activity of the livers was assessed quantitatively. Results: The Gimjeng and Chakapat extracts showed the contents of vitamin C (1.2 ± 0.6 and 4.3 ± 0.1 mg/100 g) and phenolics like trans-cinnamic acid and pelargonidin-3-O-glucoside (9.80 ± 0.21 and 19.56 ± 0.4 mg GAE/g extract, respectively), and trolox equivalent antioxidant capacity (TEAC) values (11.64 and 9.09 g/mg trolox), respectively. The Gimjeng as compared to the Chakapat demonstrated a better antioxidant activity as revealed by anti-lipid peroxidation activity with the TEAC values. Administration of CCl4 in rats elevated the serum GPT, GOT, and ALP level whereas silymarin, Gimjeng and Chakapat extracts prevented these increases significantly. Significant decrease of apoptotic cells together with restoration of morphological changes confirmed the hepatoprotective effect in the CCl4-induced rats pretreated with the extracts. Conclusion: Antioxidant properties of the Gimjeng and Chakapat lychees as evidenced by the vitamin C and phenolic compounds, anti-lipid peroxidation and anti-apoptosis could explain the hepatoprotective effects in CCl4-induced hepatotoxicity. © 2011 Elsevier Ireland Ltd.